A164 SYMPTOMATIC COLONIC SPIROCHETOSIS IN IMMUNOCOMPETENT HOSTS: A CASE SERIES. (15th March 2019) - Gozdzik, M; Sylwestrowicz, T
Abstract: Background: Intestinal spirochetosis (IS) is an uncommon disease in humans. It is caused by tightly coiled gram negative bacteria, Brachyspira spp. These bacteria are most often found incidentally on colonic biopsy specimens, adhering to the luminal cell surface. IS can, however, present with a wide range of phenotypes ranging from mild gastrointestinal upset, to disseminated infection and sepsis in immunocompromised individuals. There has been debate in the literature over whether IS is pathogenic or apathogenic, and whether it should be treated or not, as only a portion of patients improve symptomatically with treatment. Aims: To describe a case series of colonic spirochetosis in immunocompetent individuals. Methods: Two cases were identified in clinical practice and used in this case series. Results: Case 1: A 40-year-old male is referred from his family physician with a history of loose bowel movements for several years and an elevated TTG IgA. On review, he also has symptoms of reflux and dysphagia to solids, but no blood per rectum or other alarming features. An HIV test is negative. Physical and laboratory examination is unremarkable. Endoscopic examination reveals mild gastritis with no stricture, a 5mm sigmoid polyp, internal hemorrhoids and otherwise normal findings. Biopsies of the colon reveal spirochetosis. The patient is treated with a course of metronidazole 500mg PO TID for 10 days, which results in significant improvement of his symptoms. Repeat sigmoidoscopy after treatment with biopsies is negative for spirochetes. Case 2: A 22-year-old male is referred from his family physician with a two year history of vague abdominal pain and loose bowel movements. He has a family history of Crohn's disease. There is no evidence of blood per rectum, weight loss, or other alarming features. Laboratory examination reveals iron deficiency. Given his family history he is scheduled for an upper and lower endoscopy. Endoscopic examination reveals evidence of mild reflux esophagitis but is otherwise normal and colonic mucosa looks unremarkable. Biopsies of the colon reveal spirochetosis. The patient is treated with a course of metronidazole 500mg PO TID for 10 days. His symptoms improve while on treatment, then return, but to a lesser degree. Repeat colonoscopy after treatment with biopsies is negative for spirochetes. Conclusions: Spirochetes are gram negative bacilli that are often identified incidentally in colonic biopsy specimens. However, they have been shown to be highly pathogenic in immunocompromised hosts and can even provoke symptoms in immunocompetent individuals. Both our patients had symptomatic improvement, at least initially, after treating their intestinal spirochetosis. This case series raises the question of the clinical significance and possible increasing incidence of IS found in intestinal biopsy specimens. Funding Agencies: None